174 Discrimination moderates the association of sleep and cognitive function in older Black adults: The Einstein Aging Study. (3rd May 2021) - Ji, Linying; Jiao, June; Zhaoyang, Ruixue; Derby, Carol; Buxton, Orfeu; Gamaldo, Alyssa
Abstract: Introduction: Experiences of discrimination attributed to a range of individual characteristics (race, skin color, age, sex, etc.) may influence the extent to which sleep impacts cognitive functioning in order adults, particularly within older minorities. Thus, we investigated the effect of discrimination on the relationship between actigraphic sleep quality and cognitive function in analyses stratified by race. Methods: Participants (N=286, mean age=77.4 years, 32% males; 45% white, 41% Black, 14% Hispanic/others) enrolled in The Einstein Aging Study were included. Sleep disturbance, as measured by wake after sleep onset (WASO) (mean=63 min, sd=27 min), was calculated from wrist actigraphy over 15.4±1.4 days. Participants' mean ambulatory cognitive function was assessed with a validated, memory binding, smartphone-based EMA task (Color Shapes) repeated 4 times daily. A modified version of the Williams' Everyday Discrimination questionnaire, optimized for older adults, measured participants' endorsement of discriminated characteristics. Linear regressions, stratified by race (white, Black separately), were conducted with interaction terms to investigate whether discrimination moderated associations between WASO and ambulatory cognitive function. Models controlled for age, education, income, and gender. Regions of significance were also evaluated. Results: Race-stratified analysis indicated that the association between mean WASO and cognitive function was significantly moderated by the number of discriminated characteristics among Black adults (n=117), not whites (n=128). Specifically, among Black adults who identified few discriminated characteristics, WASO was not significantly associated with memory binding. However, Black adults who identified discriminated characteristics at +1 SD above the mean (5.5 traits) exhibited a 12% lower average memory binding test score (percent responses correct) with each half-hour greater mean WASO (p=.01). Analysis of the region of significance showed the association is significant when participants endorsed more than three discriminated characteristics. Conclusion: These findings emphasize the importance of considering sociocultural factors, such as discrimination, to understand the association between sleep quality and cognitive functioning, particularly for older Blacks. Support (if any): R01AG062622